2023
DOI: 10.3390/foods12081661
|View full text |Cite
|
Sign up to set email alerts
|

Habits, Health and Environment in the Purchase of Bakery Products: Consumption Preferences and Sustainable Inclinations before and during COVID-19

Abstract: The aim of the research is to investigate whether purchasing decisions about bakery products (bread, snacks and biscuits) are influenced by concerns about health, climate change, biodiversity loss and food waste. The exploratory survey was carried out in two successive moments before and during the health emergency from COVID-19. Before the health emergency, face-to-face interviews were carried out using a structured questionnaire. Data were analyzed by factor analysis, reliability tests and descriptive analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 87 publications
2
5
0
Order By: Relevance
“…This finding is in accordance with the reports published by many authors, such as Lin et al. (2000), Nicolosi et al. (2023), Boubker and Douayri (2020), and Kim and Sim (2017).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…This finding is in accordance with the reports published by many authors, such as Lin et al. (2000), Nicolosi et al. (2023), Boubker and Douayri (2020), and Kim and Sim (2017).…”
Section: Discussionsupporting
confidence: 94%
“…Thus, the platform can provide customers with opportunities for a shopping experience, improve their SAT, and enhance loyalty. This finding is in accordance with the reports published by many authors, such as Lin et al (2000), Nicolosi et al (2023), Boubker and Douayri (2020), and Kim and Sim (2017). The analysis of H2a and H2b revealed that PS had a negative effect on SAT but a positive effect on PI.…”
Section: Adaptability and Explaination Of Semsupporting
confidence: 92%
See 2 more Smart Citations
“…Over time, numerous investigations have been carried out on the science/technology of cereals and their derivatives, as they give an idea of the efforts that remain to be studied on post-process changes and thus improve applied research in studies surrounding bakery products. In this context, biscuits are versatile bakery products from the food industry that occupy a prominent position due to their attractive characteristics such as longer shelf life, and variety of flavors or textures (Arepally et al, 2020;Bölek, 2021;Nicolosi et al, 2023;Roze et al, 2023).…”
Section: Introductionmentioning
confidence: 99%